Türkiye'de siyasi temsil ve siyasi ahlâk bağlamında Güneş Motel Olayı - KÖSALİ MUŞ, Seçil (KİTOD, 2025)
AbstractThe Gunes Motel Incident that occurred after the 1977 general elections is the most important example of political representation and political moral crises. As a result of the general elections, the authority to form a government was given to the CHP led by Bülent Ecevit, despite not having a majority, and thus the first minority government in Turkish political history was established. As a result of the government not receiving a vote of confidence, the task was given to the AP led by Süleyman Demirel. Demirel established the 2nd Nationalist Front Government with the AP-MSP-MHP coalition. The CHP, which increased its votes as a result of the local elections held in 1977, met with 12 deputies who resigned from the AP at the Gunes Motel and signed a protocol. Thus, the CHP, which reached enough deputies to submit a motion of no confidence to the Parliament to bring down the 2nd MC Government, caused the fall of a government as a result of a vote of confidence for the first time in Turkish political history. In this study, the historical process of the Gunes Motel Incident, which was the first incident in Turkish political history where a deputy was transferred, its political actors and its effects on political morality and political representation were examined.

1977 yılı genel seçimlerinden sonra meydana gelen Güneş Motel Olayı siyasi temsil ve siyasi ahlâk krizlerinin en önemli örneğidir. Yapılan genel seçimler sonucunda hükümeti kurma yetkisi çoğunluğa sahip olmamasına rağmen Bülent Ecevit yönetimindeki CHP’ye verilmiş ve böylece Türk siyasi tarihinin ilk azınlık hükümeti kurulmuştur. Hükümetin güvenoyu alamaması sonucunda görev bu kez Süleyman Demirel liderliğindeki AP’ye verilmiştir. Demirel, AP-MSP-MHP koalisyonuyla II. Milliyetçi Cephe Hükümeti’ni kurmuştur. 1977 yılında yapılan yerel seçimler sonucunda oyunu artıran CHP, AP’den istifa eden 12 milletvekiliyle Güneş Motel’de görüşerek protokol imzalamıştır. Böylece II. MC Hükümeti’ni düşürmek için Meclis’e gensoru önergesi vermeye yetecek kadar milletvekili sayısına ulaşan CHP, Türk siyasi tarihinde ilk kez güven oylaması sonucunda bir hükümetin düşürülmesine sebep olmuştur. Bu çalışmada Türk siyasi tarihinde milletvekili transferinin yapıldığı ilk hadise olan Güneş Motel Olayı’nın tarihsel süreci, siyasi aktörleri ve siyasi ahlâk ve siyasi temsile etkileri incelenmiştir.
Keywords: Turkish Political Life; Gunes Motel Incedent; Ecevit; Demirel; AP; CHP; Political representation; Political morality; Deputy transfer; Güneş Motel Olayı; Ecevit; Demirel; AP; CHP; Siyasi temsil; Siyasi ahlak; Milletvekili transferi; Türk Siyasal Hayatı